Big Data for climate-smart agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
From forecasting presidential elections to predicting disease outbreaks, analysts are finding ways to turn Big Data — the immense stocks of information collected in computers worldwide — into an invaluable resource for planning and decision-making. Now, scientists at the International Center for Tropical Agriculture (CIAT) have applied Big Data tools to pinpoint strategies that work for small-scale farmers in a changing climate.